Is There a Right Time to Know?: The Right Not to Know and Genetic Testing in Children. Issue 1 (2014) - Borry, Pascal; Shabani, Mahsa; Howard, Heidi Carmen
Abstract : In the last few decades, great progress has been made in both genetic and genomic research. The development of the Human Genome Project has increased our knowledge of the genetic basis of diseases and has given a tremendous momentum to the development of new technologies that make widespread genetic testing possible and has increased the availability of previously inaccessible genetic information. Two examples of this exponential evolution are the increasing implementation of next-generation sequencing technologies in the clinical context and the expanding commercial offer of genetic tests directly-to-consumers. Firstly, the rapid development of next generation sequencing technologies (i.e., high-throughput and massively parallel DNA sequencing technologies) has substantially reduced both the cost and the time required to sequence an entire human genome. These technologies are increasingly being used in the clinical setting with the goal of diagnosing conditions of presumed genetic origin that cannot be explained by targeted sequencing approaches.